"إدارة الجودة الشاملة في المؤسسات الجزائرية _دراسة حالة مؤسسة سوف لدقيق _" - لخضر, بن محمد الصغير; عبد الرؤوف, عبد الرؤوف جنيدي; نورة, جلاخ (جامعة الوادي - University of Eloued, 2023)
" ُالملخص تعد إدارة الجودة الشاملة من المواضيع الهامة التي حظيت باهتمام كبير في بيئة الأعمال، فهي الوسيلة الأنسب و الأداة الأنجع التي تساعد المؤسسات الاقتصادية في مواجهة التحديات، حتى تتمكن من تطوير و تحسين عملياتها و أداء مختلف أنشطتها من خلال انجاز الأعمال بالطرق الحديثة و الالتزام بالمسؤولية و القيادة السليمة. لذلك هدفت هذه الدراسة إلى الحث على ضرورة تطبيق إدارة الجودة الشاملة في كافة المؤسسات الاقتصادية الجزائرية، باعتبارها وسيلة من جهة وغاية من جهة أخرى تصبوا إلى بلوغها مختلف المؤسسات الاقتصادية الجزائرية، إذ تسعى هذه الأخيرة إلى التطبيق السليم لمختلف معايير الإيزو بغرض تسهيل عمليات التصدير و الاستيراد، و هذا يؤدي إلى تحسين مستوى أدائها، و بالتالي تحقيق التميز و الريادة في السوق المحلية و العالمية. و تعتبر مؤسسة سوف للدقيق بولاية الوادي أبرز مثال على ذلك، فقد تمت دراسة نشاط المؤسسة خلال الفترة ( 2010-2022)، و تم التوصل إلى أن هذه المؤسسة تتبنى أسلوب إدارة الجودة الشاملة، من خلال جودة منتجاتها و جودة معاملتها مع العملاء، الأمر الذي أدى إلى ارتقائها و تميزها من خلال التحسين المستمر لأدائها، و بالتالي تعزيز مركزها التنفسي في ظل القطاع التي تنشط فيه. " "Summary: Total quality management is one of the important topics that have received great attention in the business environment, as it is the most appropriate and most effective tool that helps economic institutions in facing challenges, so that they can develop and improve their operations and perform their various activities through the completion of work in modern ways and adherence to responsibility and sound driving. Therefore, this study aimed to urge the need to implement total quality management in all Algerian economic institutions, as a means on the one hand and an end on the other hand that the various Algerian economic institutions aspire to achieve, as the latter seeks to apply the various ISO standards in order to facilitate export and import operations. This leads to improving its level of performance, and thus achieving excellence and leadership in the local and global market. The Souf Flour Establishment in El-Wadi State is the most prominent example of this. The activity of the Establishment was studied during the period (2010-2022), and it was concluded that this Establishment adopts the method of total quality management, through the quality of its products and the quality of its treatment with customers, which It led to its advancement and distinction through the continuous improvement of its performance, and thus strengthening its respiratory position in light of the sector in which it is active. "
Keywords: إدارة الجودة الشاملة، المؤسسات، المنتج، العملاء.; total quality management, institutions, product, customers